THE ROLE OF HOLISTIC OWNER INVOLVEMENT AS A STRATEGY TO IMPROVE FINANCIAL PERFORMANCE - Kasmawati Kasmawati; Tomy Fitrio (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
The objective of this study is to examine the impact of liquidity, financial leverage, and company size on financial performance, with the moderation of holistic owner engagement in LQ45 enterprises. The study utilizes secondary data obtained from LQ45 firms that are publicly traded on the Indonesia Stock Exchange from 2020 to 2023. The data were subjected to panel data regression analysis. The findings suggest that liquidity, financial leverage, business size, and holistic owner participation all have an impact on financial success. In addition, the level of owner engagement has a moderating effect on the impact of liquidity, financial leverage, and firm size on financial performance. This study suggests that adopting a comprehensive approach to owner involvement can be an effective strategy for enhancing the financial performance of companies that are listed on the Indonesia Stock Exchange. Previous empirical research has yet to examine the impact of comprehensive owner engagement as a moderator on enhancing financial success. According to the findings, a successful approach to enhancing financial performance is to have comprehensive owner engagement in the organization.